Digging for Dementia: Exploring the experience of community gardening from the perspectives of people with dementia. (3rd July 2018) - Noone, Sarah; Jenkins, Nicholas
ABSTRACT: Objectives: The study sought to explore the lived experiences of people with dementia who participate in community-based gardening programmes. Methods: A collaborative gardening project was conducted over six weeks at a day centre for people with dementia. Six participants were recruited from the centre's attendees. Each session was co-designed by participants. Semi-structured group interviews were conducted each week, and researcher observations were documented. Semi-structured interviews were also conducted with the centre's staff to explore their views and to contextualise gardening participants' experiences. Data were analysed inductively using thematic analysis. This paper focuses upon three of the study's emergent themes: identity, agency, and community. Results: The findings revealed that for people with dementia, gardening is not merely a matter of enjoying time outdoors; it is a forum for the articulation of identity and selfhood and expression of agency, and can facilitate the development of new social bonds based upon shared interests, rather than a shared diagnosis. Conclusion: Gardening-based interventions can offer more than simply facilitating outdoor engagement and promoting social interaction. When conditions are right, gardening can be an effective vehicle for the promotion of social citizenship and expression of selfhood and agency in dementia.